Kesejahteraan Spiritual dengan Kejadian Infeksi Oportunistik pada ODHA - Fitri Hastuti Ningsih; Rohman Azaam; Mustikasari Mustikasari (Jurnal Keperawatan Silampari, 2020)
This study aimed to identify the relationship between spiritual well-being and the incidence of opportunistic infections in PLHIV. Analytical descriptive research method with the cross-sectional approach and random sampling technique. The research univariate analysis results showed that respondents who experienced opportunistic infections â‰¤ 2 were 199 (89.2%), and respondents with moderate spiritual well-being were 127 (57%). The results of the bivariate analysis state that the chi-square test explains that there is a relationship between spiritual well-being and the incidence of opportunistic infections (p-value = 0.007), so OR = 3.689 means moderate spiritual well-being has a 3.689 chance of experiencing opportunistic infections â‰¤ two compared to PLWHA with mild spiritual well-being. Multivariate analysis showed that education was the dominant variable in the incidence of opportunistic infections (OR = 6.378). In conclusion, there is a high adherence to the incidence of opportunistic infections in PLWHA. The dominant factor in the incidence of opportunistic infections is education. Keywords: HIV, Opportunistic Infection Incidence, Spiritual Well-being